Deoxyelephantopin induces apoptosis in HepG2 cells via oxidative stress, NF‐κB inhibition and mitochondrial dysfunction. (15th September 2016) - Mehmood, Tahir; Maryam, Amara; Zhang, He; Li, Yongming; Khan, Muhammad; Ma, Tonghui
Abstract: Deoxyelephantopin (DET), a naturally occurring sesquiterpene lactone present in Chinese medicinal herb, Elephantopus scaber has been shown to exert anti‐inflammatory as well as anticancer effects in various cancer cells of human origin in vitro . However, the exact molecular mechanism underlying DET‐induced apoptosis remains largely unexplored, particularly in human hepatocellular carcinoma G2 (HepG2) cells. In the present study, we found that DET inhibits proliferation and induces apoptosis in HepG2 cells in a dose‐dependent manner. This DET‐mediated apoptosis was found to be associated with reactive oxygen species generation, glutathione depletion and decreased activity of thioredoxin reductase, mitochondrial membrane potential disruption, Bcl‐2 family proteins modulation, cytochrome c release, caspases‐3 activation, PARP cleavage and inhibition of NF‐κB activation. DET inhibited the constitutive as well as induced‐translocation of NF‐κB into nucleus and augmented the apoptotic effect of Gemcitabine. IKK‐16 (NF‐κB inhibitor) further enhanced the cytotoxicity of DET and gemcitabine indicating that DET induces apoptosis in HepG2 cells at least partially through inhibition of NF‐κB activation. Further mechanistic study demonstrated that DET inhibits the translocation of constitutive as well as induced‐NF‐κB into nucleus by decreasing phosphorylation of IкBα. Moreover, pretreatment of cells with 3 mM NAC reversed DET‐mediated cell death and NF‐κB inhibition, indicating that DET exerts its anticancer effects mainly through oxidative stress. Therefore, DET may be developed into a lead chemotherapeutic drug as a single agent or in combination with clinical drugs for the effective treatment of liver cancer. © 2016 BioFactors, 43(1):63–72, 2017